Etika dan Strategi Komunikasi Dakwah Islam Berbasis Media Sosial di Indonesia - Samsudin, Dafrizal; Putri, Indah Mardini (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2023)
The development of social media in the digital era has a broad influence on many dimensions of human life, including Islamic da'wah activities. Today, many da'i da'wah efforts use various social media platforms as da'wah channels. This article aims to look at various ethical issues and Islamic and Da'wah communication strategies used by Islamic preachers based on social media channels. Qualitatively, the method of writing this article is in the nature of a literature study by collecting data from the Sinta Journal and Garuda Research and Technology Dikti databases. The scope and focus of the search for articles is specifically on the theme of ethics and communication strategies and social media-based da'wah with searches based on the Google Scholar search engine. Supporting data is from books and other relevant reference sources. The results of this study found that ethically, Indonesian da'wah communicators carry out da'wah communication through social media placing the al-Qur'an, al-Hadith, namely qoulan ma'rufan, qoulan kariman, qoulan maysuran, qoulan balighan, qoulan layyinan, and qoulan sadidan as foundation for the development of an attitude of openness, fairness, courtesy, honesty, responsibility, constructiveness and hope for the ridho of Allah. Strategically, da'wah communicators maximize the space of social media platforms as a means of da'wah by filling in creative Islamic content by considering aspects of new insights and knowledge, touching emotions, language that is easy to understand, using visual and graphic technology and is attractive.